Impact of inhaled treprostinil on risk stratification with noninvasive parameters: a post hoc analysis of the TRIUMPH and BEAT studies. (1st December 2020) - Tonelli, Adriano R.; Sahay, Sandeep; Gordon, Kathryn W.; Edwards, Lisa D.; Allmon, Andrew G.; Broderick, Meredith; Nelsen, Andrew C.
Abstract : The 2015 European Society of Cardiology/European Respiratory Society treatment guidelines recommend frequent risk assessment in pulmonary arterial hypertension utilizing risk variables. Our objectives were: (1) to investigate the impact of inhaled treprostinil on risk stratification using the French noninvasive approach and REVEAL 2.0, and (2) to analyze the prognostic utility of both risk stratification methods in the predominantly New York Heart Association/World Health Organization functional class III/IV cohorts of TRIUMPH and BEAT. A post hoc analysis was performed to assess risk at baseline and follow‐up at Week 12 in the TRIUMPH cohort ( n  = 148) and at Week 16, 21, and 30 in the inhaled treprostinil naïve placebo BEAT cohort ( n  = 73). Overall survival, clinical worsening‐free survival, and pulmonary arterial hypertension‐related hospitalization‐free survival were all assessed in the pooled TRIUMPH and inhaled treprostinil naïve placebo BEAT cohorts based on risk group/strata at Week 12/16 follow‐up. Inhaled treprostinil improved REVEAL 2.0 risk stratum (OR: 2.38, 95% CI: 1.09–5.19, p  = 0.0298) and REVEAL 2.0 score ( p  = 0.0008) compared to placebo in the TRIUMPH cohort at Week 12. REVEAL 2.0 risk stratum and the number of low‐risk criteria by the French approach improved at Weeks 16, 21, and 30 in the inhaled treprostinil naïve placebo BEAT cohort. Combining cohorts, REVEAL 2.0 risk stratification at follow‐up was prognostic for clinical worsening‐free, pulmonary arterial hypertension hospitalization‐free, and overall survival, whereas the number of low‐risk criteria was not. These post‐hoc pooled analyses suggest inhaled treprostinil improves risk status and indicates that the REVEAL 2.0 calculator may be more suitable than the French noninvasive method for evaluating short‐term clinical change in the New York Heart Association/World Health Organization functional class III/IV population.